Alterations in function and expression of ABC transporters at blood-brain barrier under diabetes and the clinical significances - Liu, Li; Liu, Xiaodong (Frontiers in Pharmacology, 2014)
Diabetes is a systematic metabolic disease, which often develops a number of well-recognized vascular complications including brain complications which may partly result from the dysfunction of blood-brain barrier (BBB). BBB is generally considered as a mechanism for protecting the brain from unwanted actions resulting from substances in the blood and maintaining brain homeostasis via monitoring the entry or efflux of compounds. ATP-binding cassette (ABC) family of transporters including P-glycoprotein (P-GP) and breast cancer-related protein (BCRP), widely expressed in the luminal membrane of the microvessel endothelium and in the apical membrane of the choroids plexus epithelium, play important roles in the function of BBB. However, these transporters are easily altered by some diseases. The present article was focused on the alteration in expression and function of both P-GP and BCRP at BBB by diabetes and the clinical significances.